PEMANFAATAN JURNAL REFLEKSI SEBAGAI STRATEGI METAKOGNITIF DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA - Faizin, Khoirul (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2018)
Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya keaktifan peserta didik dalam pembelajaran yang berdampak pada rendahnya hasil belajar peserta didik. Secara teoritis, pemanfaatkan jurnal refleksi sebagai strategi metakognitif dapat meningkatkan keaktifan dan hasil belajar peserta didik. Penelitian ini bertujuan untuk mendeskripsikan manfaatkan jurnal refleksi sebagai strategi metakognitif dalam meningkatkan keaktifan dan hasil belajar matematika peserta didik pada materi Kesebangunan Bangun Datar. Jenis penelitian ini adalah penelitian tindakan kelas yang terdiri atas 3 siklus. Subjek pada penelitian ini adalah peserta didik kelas IX-A SMPN 2 Winongan. Pada saat proses penelitian, pengamatan dilakukan terhadap pengelolaan pembelajaran dan keaktifan belajar peserta didik. Pada akhir setiap siklus, diberikan tes hasil belajar matematika. Data yang diperoleh kemudian dianalisis dengan statistik deskriptif. Hasil analisis data menunjukkan bahwa pembelajaran dengan memanfaatkan jurnal refleksi sebagai strategi metakognitif dapat meningkatkan keaktifan dan hasil belajar peserta didik kelas IX-A SMPN 2 Winongan pada materi Kesebangunan Bangun Datar. Dengan demikian, disarankan kepada guru khususnya guru matematika untuk memanfaatkan jurnal refleksi sebagai strategi metakognitif dalam meningkatkan keaktifan dan hasil belajar peserta didik. Abstract <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false IN X-NONE AR-SA <![endif]–><span style="font-size: 10.0pt; line-height: 115%; font-family: ’Book Antiqua’,’serif’; mso-fareast-font-family: Calibri; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The background of this study was the low activeness of students in learning that impacted on the low learning outcomes. Theoretically, metacognitive strategies utilizing reflection journals can improve the activeness and learning outcomes. The purpose of this study was to describe the learning that utilizes reflective journal as a metacognitive strategy in improving the activity and the result of learning mathematic material of congruent flat surface. This research was classroom action research consisting of 3 cycles, and the subject was the student of class IX-A SMPN 2 Winongan. In the process, observation of the management of learning and student learning activities was done. At the end of each cycle, a mathematics achievement test was given. The data obtained were analyzed by descriptive statistics. The result of data analysis showed that learning by using reflective journal as a metacognitive strategy can increase the students’ activeness and their learning outcomes of congruent flat surface material. Then, It is suggested to teachers, especially math teachers to utilize reflective journals as a metacognitive strategy and choose it as an alternative in improving students’ activeness and their learning outcomes. <span style="font-size: 10.0pt; line-height: 115%; font-family: ’Book Antiqua’,’serif’; mso-fareast-font-family: Calibri; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">background of this study was the low activeness of students in learning that impacted on the low learning outcomes. Theoretically, metacognitive strategies utilizing reflection journals can improve the activeness and learning outcomes. The purpose of this study was to describe the learning that utilizes reflective journal as a metacognitive strategy in improving the activity and the result of learning mathematic material of congruent flat surface. This research was classroom action research consisting of 3 cycles, and the subject was the student of class IX-A SMPN 2 Winongan. In the process, observation of the management of learning and student learning activities was done. At the end of each cycle, a mathematics achievement test was given. The data obtained were analyzed by descriptive statistics. The result of data analysis showed that learning by using reflective journal as a metacognitive strategy can increase the students’ activeness and their learning outcomes of congruent flat surface material. Then, It is suggested to teachers, especially math teachers to utilize reflective journals as a metacognitive strategy and choose it as an alternative in improving students’ activeness and their learning outcomes.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false IN X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>